Harare city council inter-departmental office automation system - Mukano, Shepherd (Midlands State University, 2015)
This is an original documentation of the system entitled Harare city council interdepartmental office automation system. The system has been designed under the software development life cycle standards and has been development from the current problems currently encountered within this organisation. The Harare city council is relatively a very large organisation and operates under a number of departments and divisions. The offices a distributed around Harare and inter departmental collaboration is a great challenge in the organisation since its offices are scattered around. The Harare city council interdepartmental office automation have however designed as a solution to this problems and allows employees to work remotely from their office without traveling to and fro one office. All members who will be working in different offices are going to be allocated accounts and the user will view and edit information according to their access levels. The system is going to allow registered members in the management level to create a budget, make requisition, archive their important documents and share information according to the their area of specialisation